Gambaran Self Control pada High Engagement Gamer yang Bermain MMORPG - Vivekananda Lengkong; Ignatius Darma Juwono (Universitas Katolik Indonesia Atma Jaya, 2015)
Online gaming, as fun as it is, has the potential to create problems of playing excessively. Even though many people play excessively and have problems on their daily functioning, there are excessive game players who function well in their daily life (Charlton, 2010). This might be caused by good self-control in the individuals. Self-control is defined as the ability to control thoughts, emotion, behavior, and wishes in order to attain higher reward (goals) and avoid being punished or having negative consequences (Vohs, dkk., 2008). Self control will affect someone in conflicting situation among different things. This research aims to seek self control components and processes among non problematic MMORPG gamers. In depth interview with two non problematic MMORPG gamers revealed that they both have high standards to be achieved and ensure its attainment by using both cognitive and behavioral